Liquid Consumer Security - Atanasova, Aleksandrina; Eckhardt, Giana M; Husemann, Katharina C (Journal of Consumer Research, 2024)
Abstract Systemic risks––pandemics, economic recessions, professional precarity, political volatility, and climate emergencies––increasingly erode previously taken-for-granted stabilities and consumers’ confidence in the future. How do consumers manage risk and uncertainty when economic and ontological security are on the decline? Traditionally, consumers have built a sense of security through solid consumption (e.g., home ownership, accumulating possessions). A four-year ethnography of digital nomadism, however, demonstrates that looming uncertainty can render solid consumption a source of vulnerability and an unwanted anchor in turbulent times that call for agility and adaptability. We outline the emergence of liquid consumer security, defined as a form of felt security that stems from avoidance of solid consumption and its risks and responsibilities. Liquid consumer security inheres in the absence of ownership, attachments, or rootedness, and is derived from circumventing the temporal demands, financial liabilities, and commitments that solid consumption requires, which emerge as sources of risk. It is achieved through a recursive process of engaging in three strategies: (1) solid risk minimization; (2) security reconstruction through the liquid marketplace; and (3) ideological legitimation. Contributions to consumer risk and security, liquid consumption, social theories of risk, and digital nomadism are discussed.